India as Knowledge Superpower Strategy for Transformation - Planning Commission (Planning Commission, 2001)
Taking cognizance of the mission given to the country by our Prime Minister to build knowledge based activities as a major economic and social resource, the Planning Commission set up a Task Force to prepare the road map that would make India a major knowledge power within this decade. This was by no means an easy task. There is no straight and smooth road to the last mile. However, achievement of global acclaim in the field of computer software in the last few years has given us the confidence to aspire to achieve higher goals in all fields.
Planning Commission, Government of India